TRANSFORMASI OPERASIONAL INDUSTRI GARAM MELALUI TEKNOLOGI MODERN: STUDI KONSEPTUAL PADA PT LADANG GARAM NASIONAL - Ilyani, Dian; Syah, Tantri Yanuar Rahmat; Negoro, Dimas; Ruswanti, Endang (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to evaluate the application of technology in the salt processing process to improve operational efficiency and product quality and minimise waste of resources, time, and costs by identifying the challenges and opportunities faced in implementing technology in industrial salt processing, both from the technical, operational, and market aspects.Method: Descriptive analysis through descriptive methods with a literature review approach related to the operational planning of salt processing technology and the salt processing industry business. Data was collected through journals, reports, and documents on technology-based salt processing..Result: The implementation of technology in the production process, such as the use of automated machines, Internet-based monitoring systems, and digital data management, can increase work efficiency, reduce production time, and minimise the potential for human error. Technology enables more consistent production standards, ensuring that the quality of industrial salt produced meets market specifications and customer needs across various sectors, including pharmaceutical, chemical, and food. This research is one of the first conceptual studies to explicitly discuss the operational transformation of the salt industry in Indonesia, particularly at the national company level, such as PT Ladang Garam Nasional, utilising an Industry 4.0 technology approach. The contribution of this research is to provide a technology implementation framework for the salt manufacturing sector, serving as a reference study for other traditional sectors (agriculture, fisheries, etc.) to transform through the adoption of digital technology. Keywords: Industrial Salt, Caustic Soda, Modern Technology, Operational Planning